Oncogenic Hijacking of the PIN1 Signaling Network - Zannini, Alessandro; Rustighi, Alessandra; Campaner, Elena; Del Sal, Giannino (Frontiers in Oncology, 2019)
Cellular choices are determined by developmental and environmental stimuli through integrated signal transduction pathways. These critically depend on attainment of proper activation levels that in turn rely on post-translational modifications (PTMs) of single pathway members. Among these PTMs, post-phosphorylation prolyl-isomerization mediated by PIN1 represents a unique mechanism of spatial, temporal and quantitative control of signal transduction. Indeed PIN1 was shown to be crucial for determining activation levels of several pathways and biological outcomes downstream to a plethora of stimuli. Of note, studies performed in different model organisms and humans have shown that hormonal, nutrient, and oncogenic stimuli simultaneously affect both PIN1 activity and pathways that depend on PIN1-mediated prolyl-isomerization, suggesting the existence of evolutionarily conserved molecular circuitries centered on this isomerase. This review focuses on molecular mechanisms and cellular processes regulated by PIN1 in physiological conditions like proliferation, metabolism, and stem cell fate, in response to different stimuli, discussing how these are subverted in and hijacked by cancer cells. Current status and open questions regarding the use of PIN1 as biomarker and target for cancer therapy as well as clinical development of PIN1 inhibitors is also addressed.